Lactate as a Potential Biomarker of Sepsis in a Rat Cecal Ligation and Puncture Model - Xiaozhu Zhai; Zhengfei Yang; Guanghui Zheng; Tao Yu; Peng Wang; Xuefen Liu; Qin Ling; Longyuan Jiang; Wanchun Tang (Hindawi Limited, 2018)
We attempted to investigate whether blood lactate is a useful biomarker for sepsis in a rat cecal ligation and puncture (CLP) model. Male Sprague-Dawley rats underwent approximately 75% cecum ligation and two punctures to induce high-grade sepsis. A lactate of 1.64 mmol/L (Youden score of 0.722) was selected as the best cutoff value to predict the onset of sepsis after CLP exposure; 46 of 50 rats who survived 24 hours after the CLP were divided into the L group (lactate < 1.64 mmol/L) and M group (lactate ≥ 1.64 mmol/L). In the M group, the animals had significantly higher murine sepsis scores and none survived 5 days post-CLP, and the rate of validated septic animals, serum procalcitonin, high mobility group box 1, blood urea nitrogen, alanine transaminase, cardiac troponin I, and the wet-to-dry weight ratio were significantly higher compared to the L group. Worsen PaO2/FiO2, microcirculations, and mean arterial pressure were observed in the M group. More severe damage in major organs was confirmed by histopathological scores in the M group compared with the L group. In conclusion, lactate ≥ 1.64 mmol/L might serve as a potential biomarker to identify the onset of sepsis in a rat CLP model.